IFAS Assessment of the Status of Non-Native Plants in Florida’s Natural Areas - Alison M. Fox; Doria R. Gordon; Joan A. Dusky; Linda Tyson; Randall K. Stocker (EDIS)
The purpose of this assessment is to provide a well-defined mechanism by which all IFAS Extension publications can conform in their description and categorization of non-native plants that are invading natural areas in Florida. The objective of this assessment is to summarize relevant ecological, management and economic value information on species. The intention is to provide a level of information divided into relevant categories that is greater and more functional than that indicated by simple presence or absence from an “Invasive Species List.” This document is SS-AGR-225, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Revised publication date: July 2004.